Pengembangan Kedai Brugak Ramah Lingkungan di Bukit Batu Gendang dalam Mendukung Pariwisata di Desa Giri Sasak Kuripan Lombok Barat - Riawan, Awinda Sari (Politeknik Pariwisata NHI Bandung, 2025)
Bukit Batu Gendang is one of the tourist destinations in Giri Sasak Village in Kuripan District, West Lombok Regency which is in the Hill Range area in West Nusa Tenggara Province. The location which is located in a hill area has the potential to be developed as a tourist village. There is much that can be developed in this tourist village in the future. However, currently what will be focused on first is the potential for developing the kedai brugak, especially developing an environmentally friendly brugak kedai which will be located on Batu Gendang Hill. The aim of this Community Service activity is to help develop the brugak kedai to increase tourism potential in Giri Sasak village, especially Bukit Batu Gendang. The service carried out is to develop the brugak kedai into a leading tourist attraction. Increased awareness of the brugak (brugak kedai) management team and employees regarding the importance of environmentally friendly practices in managing brugak kedai, especially brugak (brugak kedai), small changes such as using paper straws, reducing the use of single-use plastic, and sorting waste. Reducing the amount of waste produced by brugak kedai, both solid and liquid waste. Developing a brugak (kedai brugak) business model that prioritizes environmental and social sustainability. The service was carried out by providing equipment and supplies for the kedai to be able to operate again. Apart from that, signboards for kedai, swimming pools, directions and other tourist information were also handed over.